An Assessment of Clinical and System Drivers of Family Satisfaction in the PICU*. Issue 10 (October 2020) - Hummel, Kevin; Presson, Angela P.; Millar, Morgan M.; Larsen, Gitte; Kadish, Howard; Olson, Lenora M.
Abstract : Objective: Investigate clinical and system drivers of family satisfaction in the PICU. Design: Mixed methods qualitative and quantitative (observational) study. Qualitative interviews with families were performed as a pilot to inform modality of survey distribution based on family preferences. A validated pediatric satisfaction survey deployed to family members for 7 months with a corresponding chart review and administrative data collection. Setting: PICU in a tertiary children's hospital. Patients: Two hundred six families of patients admitted to the PICU more than 48 hours. Interventions: None. Measurements and Main Results: Families preferred surveys distributed electronically on a tablet in the PICU setting. The Pediatric Family Satisfaction-ICU survey was used to assess comfort with medical decision-making and communication with the care team. Capture rate of all eligible patients was 69.5% and response rate was 90.8%. Overall, 64.7% of respondents were highly satisfied, whereas over one third were not highly satisfied; families of Hispanic ethnicity (odds ratio of lower satisfaction of families with Hispanic ethnicity: 2.09; 95% CI, 1.01–4.33; p = 0.047) and high social stressors (odds ratio of higher satisfaction among high stressed subgroup: 0.49; 95% CI, 0.24–0.99; p = 0.047) reported statistically significant lower satisfaction. Additional free-text responses were identified in 21% of respondents, with the majority of comments indicating wishes for improvements clustered around communication with the medical team or sleeping environment of families and patients. Conclusions: High capture rates of family satisfaction in the PICU can be obtained with a PICU-specific survey, limiting barriers to completion by including family preferences, and distributing in the PICU setting. Less than two-third of PICU families are highly satisfied; patients of Hispanic ethnicity and those with high social stressors predict low satisfaction, whereas illness severity, age, and PICU length of stay did not have statistical significance. Local improvement teams can use this approach to drive enhanced satisfaction. Abstract : Supplemental Digital Content is available in the text.